The expert witness, forensic science, and the criminal justice systems of the UK - Hackman, Lucina; Raitt, Fiona E.; Black, Sue M. (Boca Raton : CRC Press, 2016)
The global nature of crime often requires expert witnesses to work and present their conclusions in courts outside their home jurisdiction with the corresponding need for them to have an understanding of the different structures and systems operating in other jurisdictions. This book will be a resource for UK professionals, as well as those from overseas testifying internationally, as to the workings of all UK jurisdictions. It also will help researchers and students to better understand the UK legal system.
OCLC-licensed vendor bibliographic record.
Keywords: Evidence, Expert -- Great Britain; Criminal justice, Administration of -- Great Britain; Forensic sciences -- Great Britain; LAW / Civil Procedure; LAW / Legal Services; POLITICAL SCIENCE / Government / Judicial Branch; LAW / Forensic Science; LAW / Criminal Law / General